PERAMALAN KEDATANGAN WISATAWAN MANCANEGARA INDONESIA: METODE HOLT’S WINTER EXPONENTIAL SMOOTHING - Fajar Islamiyah Rahmawati; Nurafni Eltivia; Kartika Dewi Sri Susilowati (Media Mahardhika, 2020)
This reseacrh aims to predict the arrival of foreign tourists in Indonesia using the Exponential Smoothing method. This research is quantitative descriptive. The data used are data of foreign tourist arrivals according to nationality taken from the Badan Pusat Statistik. Data is managed through the Microsoft Excel application. In determining RMSE, Solver Parameter help is used in Microsoft Excel to determine the lowest error rate. The data used in this research indicate that there are trend and seasonal patterns, so the most suitable Exponential Smoothing method is the Holt's Winter Exponential Smoothing method. The results of this research indicate that foreign tourist arrivals in Indonesia are predicted to increase in 2020. The results of this research are expected to help the government and related agencies in planning and decision making in the tourism industry.